1964
DOI: 10.1083/jcb.22.2.403
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation and Fate of H3-Tyrosine in the Hair Cortex of Rats Observed by Radioautography

Abstract: The incorporation of H3-tyrosine into the protein of the cells in the cortex of rat hair has been investigated by radioautography. In growing hairs, radioactivity is found in the matrix, the upper bulb, and the whole of the keratogenous zone up to the fully keratinized part of the shaft, 10 and 30 minutes after an injection of labelled tyrosine. This is unequivocal evidence of protein synthesis at these sites. There is a very precise relationship between the end of protein synthesis and the hardening of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1966
1966
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…From a consideration of the cell dynamics of hair growth, it has been shown that the volume of hair produced in unit time (Vt) can be expressed by the equation Vt = Q x Vm x Rm x Iv, where Q is the proportion of matrix cells entering the hair shaft proper, Vm is the volume of the hair matrix, Rm is the proportion of matrix cells that divide in unit time, and Iv is the relative increase in cell volume (Sims, 1965). Changes in all of the variables on the right-hand side of the equation could contribute to the gross depression of hair growth in kwashiorkor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a consideration of the cell dynamics of hair growth, it has been shown that the volume of hair produced in unit time (Vt) can be expressed by the equation Vt = Q x Vm x Rm x Iv, where Q is the proportion of matrix cells entering the hair shaft proper, Vm is the volume of the hair matrix, Rm is the proportion of matrix cells that divide in unit time, and Iv is the relative increase in cell volume (Sims, 1965). Changes in all of the variables on the right-hand side of the equation could contribute to the gross depression of hair growth in kwashiorkor.…”
Section: Discussionmentioning
confidence: 99%
“…It is formed from cells which are generated in the matrix of the hair bulb and move towards the skin surface. As the cells of the hair cortex migrate from the matrix to the fully keratinized region of the hair they rapidly synthesize and accumulate proteins (Sims, 1964). Any factor that depresses the rate at which cells in general synthesize proteins could produce changes in hair growth by lowering the mitotic rate of cells in the hair matrix, and by reducing the amount of protein accumulated in the cortical cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The order of differentiation/keratinization of the respective cell layers in general parallels that of bulbar flow stream rates (with an exception noted in the case of Huxley's layer). Similarly, the shaft outer cortex keratinizes earlier than its inner cortex (Sims, ).…”
Section: Hair Curvature: Mechanical and Morphological Considerationsmentioning
confidence: 99%
“…The cells generated migrate towards the surface of the skin and differentiate into the components of the hair shaft and its sheaths. An experiment performed on rats at the Anatomy Department of McGill University (Sims, 1964) showed that the rate of protein synthesis per unit volume of tissue increased 3-fold from the mitotic cells to the differentiating cells of the hair cortex. Since the differentiating cells are 4 times the volume of the mitotic cells the equivalent of the protein mass of one mitotic cell is manufactured by each differentiating cell every hour.…”
Section: Haie Growth As An Index Of Protein Synthesismentioning
confidence: 99%